Infectious Complications and Immune/Inflammatory Response in Cardiogenic Shock Patients: A Prospective Observational Study - Parenica, Jiri; Jarkovsky, Jiri; Malaska, Jan; Mebazaa, Alexandre; Gottwaldova, Jana; Helanova, Katerina; Litzman, Jiri; Dastych, Milan; Tomandl, Josef; Spinar, Jindrich; Dostalova, Ludmila; Lokaj, Petr; et al. (Shock (Augusta, Ga.), 2017)
INTRODUCTION: Patients with cardiogenic shock (CS) are at a high risk of developing infectious complications; however, their early detection is difficult, mainly due to a frequently occurring noninfectious inflammatory response, which accompanies an extensive myocardial infarction (MI) or a postcardiac arrest syndrome. The goal of our prospective study was to describe infectious complications in CS and the immune/inflammatory response based on a serial measurement of several blood-based inflammatory biomarkers. METHODS: Eighty patients with CS were evaluated and their infections were monitored. Inflammatory markers (C-reactive protein, procalcitonin, pentraxin 3, presepsin) were measured seven times per week. The control groups consisted of 11 patients with ST segment elevation myocardial infarction without CS and without infection, and 22 patients in septic shock. RESULTS: Infection was diagnosed in 46.3% of patients with CS; 16 patients developed an infection within 48 h. Respiratory infection was most common, occurring in 33 out of 37 patients. Infection was a significant or even the main reason of death only in 3.8% of all patients with CS, and we did not find statistically significant difference in 3-month mortality between group of patients with CS with and without infection. There was no statistically significant prolongation of the duration of mechanical ventilation associated with infection. Strong inflammatory response is often in patients with CS due to MI, but we found no significant difference in the course of the inflammatory response expressed by evaluated biomarkers in patients with CS with and without infection. We found a strong relationship between the elevated inflammatory markers (sampled at 12 h) and the 3-month mortality: the area under the curve of receiver operating characteristic ranged between 0.683 and 0.875. CONCLUSION: The prevalence of infection in patients with CS was 46.3%, and respiratory tract infections were the most common type. Infections did not prolong statistically significantly the duration of mechanical ventilation and did not increase the prevalence of hospital mortality in this high-risk CS population. CS due to acute myocardial infarction was accompanied by a strong and highly variable inflammatory response, but it did not reach the intensity of the inflammatory response observed in patients with septic shock. An extensive immune/inflammatory response in patients with CS is linked to a poor prognosis.
Keywords: Male; biologické markery; Risk Factors; ROC Curve; Biomarkers; mortalita v nemocnicích; prognóza; sérový amyloidový protein; C-reaktivní protein; Aged; Prospective Studies; kalcitonin; mužské pohlaví; senioři; kardiogenní šok; Shock, Cardiogenic; infarkt myokardu; Hospital Mortality; peptidové fragmenty; senioři nad 80 let; Shock, Septic; lidé; ženské pohlaví; Humans; septický šok; Myocardial Infarction; Lipopolysaccharide Receptors; rizikové faktory; Aged, 80 and over; Calcitonin; Prognosis; lipopolysacharidové receptory; C-Reactive Protein; Peptide Fragments; Female; ROC křivka; lidé středního věku; Serum Amyloid P-Component; Middle Aged; prospektivní studie